KAMPANYE SOSIAL BUDIDAYA SAYUR MELALUI SISTEM HIDROPONIK DI KOTA PALEMBANG - Dewi Ero Wati; Aji Windu Viatra; Mukhsin Patriansah (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract: Farming activities are more specific to the agricultural sector which can support the economic needs of the community. People have become accustomed to doing the conventional system in agriculture, namely by cultivating the land first and then waiting for the rain to fall is the right time to plant. Of course, this is not an effective activity when compared between the past and today as it is today. The research method used in this design is 5W+2H Public knowledge about the use of vegetable cultivation through hydroponic systems is still minimal and no one has made social campaigns about vegetable cultivationthrough hydroponic systems, then it is necessary to design a social campaign for vegetable cultivation through a hydroponic system in Palembang City by making the main media motion graphic videos on how to cultivate vegetables through a hydroponic system which is expected to make the target target to understand how to cultivate vegetables through a hydroponic system by utilizing makeshift land and willing to practice it at home so that starting from a small environment the community can be self-sufficient in food.